PENGARUH PENERAPAN LESSON STUDY DAN PENILAIAN KINERJA TERHADAP HASIL BELAJAR FISIKA DASAR I DENGAN MENGONTROL INTELIGENSI MAHASISWA - FERDY DUNGUS (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2013)
The purpose of this research is to investigate the influence of lesson study and performance assessment towards th achievement of Basic Physics I after controlling the students’ intelligence. The research was an experimental in FMIPA UNIMA. The research sampling was obtained with multistage random sampling. Data was analyzed using two ways analyzed of covarian (ANCOVA) by design factorial of experimental method 2 x 2. The research results are as follow: 1) the achievement in Basic Physics I of the students group who learn the lesson study is higher than that of those who were taught by using conventional learning method, 2) the achievement in Basic Physics I of the students group who were given performance assessment is higher than that of those who were given written assessment test, 3) there is an interaction between learning activity and assessment toward the achievement in Basics Physics I, 4) the achievement in Basic Physics I of the students group who learnt the lesson study and was given the performance assessmentis higher than that of those who were taught by using conventional method and given performance assessment, 5) the achievement in Basic Physics I of the students group who learnt the lesson study and was given the written performance assessmentis higher than that of those who studied by using conventional method and was given the written assessment. The research result recommends that the lecturers use the lesson study in the learning process and pay attention to the assessment and the method used.